Healthcare access, symptom burden, and psychological impact in hypertrophic cardiomyopathy: a multinational patient-driven survey - Emil Tsenov; Jolanda Van der Velden; Matteo Pinciroli; Maurizio Pieroni; Franco Cecchi; Iacopo Olivotto; Niccolò Maurizi (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background and aims: Hypertrophic cardiomyopathy (HCM) is a complex genetic heart disease with significant clinical, psychological, and socioeconomic implications. While research has focused on pathophysiology and treatment, patient-reported experiences remain underexplored. Methods: A cross-sectional, multinational online survey was distributed between December 2024 and February 2025, targeting individuals diagnosed with HCM in Europe. The questionnaire included sections on demographics, symptom burden, impact on daily life, medical management, and psychological well-being. Data were analyzed descriptively, with subgroup analyses based on geography, employment, and healthcare access. Results: A total of 337 qualifying participants from 18 European countries completed the survey. They were mainly diagnosed because of symptoms (107, 42 %). Specifically, shortness of breath and fatigue had an overall high impact on quality of life, both at diagnosis and at the time of survey (3.09/5 vs 2.93/5; 3.23/5 vs 3.46/5, respectively). With HCM diagnosis, the proportion of patients engaged in low to moderate activities increased significantly (87 % vs 50 %, p < 0.01) and one major psychological complaint was weight gain (71, 49 %). Twenty-two (15 %) patients reported having lost their job because of HCM; 46 (14 %) reported a limitation in working hours as well as limitation in the kind of work performed (32, 9 %), due to the disease. Despite a significant psychological burden access to mental health support was limited, as only 15 % of patients regularly consulted a psychologist. Conclusions: This survey highlights critical gaps in HCM management, including healthcare accessibility, persistent symptom burden, and unmet psychological needs. Improved care pathways, mental health integration, and workplace accommodations are essential to enhance patient-centered HCM management across Europe.